(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Copper sulphate is highly valued for its fungicidal and algaecidal qualities, making it one of the most commonly used agrochemicals and aquaculture treatments in the world. In spite of the fact that it has a number of applications, copper sulphate has become a substantial contaminant in freshwater systems. This is mostly the result of runoff from agricultural land, effluent discharge, and excessive usage in aquaculture. The emphasis of this study is on the intricate ways in which copper sulphate influences the reproductive physiology of freshwater teleost fishes. This group of fishes accounts for a significant amount of the biological variety found in freshwater environments and is essential for maintaining ecological equilibrium and economic subsistence. The processes of hormonal dysregulation, which disrupt the endocrine system that controls gonadal development, gametogenesis, and reproductive behaviours, have given a lot of attention. These mechanisms are responsible for the failure of reproductive success. Copper’s interaction with the hypothalamic-pituitary-gonadal (HPG) axis, its generation of oxidative stress, its interference with steroidogenesis, and its disruption of hormone signalling cascades are all investigated in great detail. This review further explores the ramifications of these hormonal imbalances on the dynamics of fish populations and aquatic ecosystems. It also highlights upcoming research paths and analyses the obstacles that are now being faced in identifying and mitigating the effects of copper toxicity for fish populations.